Use of the Temperament and Character Inventory to describe the effectiveness of Gestalt therapy - Calvet, Benjamin; Vallejo, Jean-Luc; Plu, Yves; Soulat, Isabelle; Foucher, Alexandra; Clément, Jean-Pierre (Frontiers in Psychiatry, 2025)
BackgroundGestalt therapy (GT) is a dynamic, integrative, embodied approach that addresses human existence as a fundamentally relational modality, in which the experience of the self is situated in a dynamic organism–environment field. Assessments of GT are scarce, often avoided, and generally qualitative. The Therapy Gestalt TCI (THEGETCI) study aimed to show that the modifiable character dimensions of the 125-item Temperament and Character Inventory (TCI-125), as well as other personality temperament dimensions and emotional measures, change after a GT program.MethodsA psychotherapeutic program consisting of 33 one-hour sessions (minimum of 12 sessions), spaced over several months, was offered to 319 subjects with mood and/or anxiety disorders. The TCI-125, Hospital Anxiety and Depression Scale, and visual analog scale (VAS) were used to assess subjective psychological states before and after the program. All TCI-125 scores were adjusted for potential confounding factors.ResultsStatistically significant differences between the initial and final mean scores were observed for anxiety (t = 16.46; p < 0.0001), depression (t = 11.24; p < 0.0001), and harm avoidance (t = 8.82; p < 0.0001), and global psychological distress assessed by VAS (t = 18.7; p < 0.0001) (all showing decreased scores). Significant increases were observed for the three maturity dimensions: Self-Directedness (t = −11.49; p < 0.0001), Cooperativeness (t = −2.77; p < 0.006), and Self-Transcendence (t = −4.52; p < 0.0001).ConclusionThe THEGETCI study is one of the first to demonstrate the effectiveness of specific, current GT strategies on personality dimensions using rigorous evaluation methods. Further research is needed to confirm these results and to better identify both the expected benefits for practitioners and the problem profiles most likely to benefit from GT.